2012
DOI: 10.1152/japplphysiol.01290.2011
|View full text |Cite
|
Sign up to set email alerts
|

Validity of hip-mounted uniaxial accelerometry with heart-rate monitoring vs. triaxial accelerometry in the assessment of free-living energy expenditure in young children: the IDEFICS Validation Study

Abstract: One of the aims of Identification and Prevention of Dietary- and Lifestyle-Induced Health Effects in Children and Infants (IDEFICS) validation study is to validate field measures of physical activity (PA) and energy expenditure (EE) in young children. This study compared the validity of uniaxial accelerometry with heart-rate (HR) monitoring vs. triaxial accelerometry against doubly labeled water (DLW) criterion method for assessment of free-living EE in young children. Forty-nine European children (25 female, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
2
16
2
1
Order By: Relevance
“…This observation is in disagreement with the findings of Ojiambo et al (32) , who reported that a higher amount of the variation in AEE and TEE in children aged 4-10 years was explained when adding both heart rate and counts, assessed by means of a uniaxial accelerometer (ActiTrainer), to the same model.…”
Section: Discussioncontrasting
confidence: 99%
“…This observation is in disagreement with the findings of Ojiambo et al (32) , who reported that a higher amount of the variation in AEE and TEE in children aged 4-10 years was explained when adding both heart rate and counts, assessed by means of a uniaxial accelerometer (ActiTrainer), to the same model.…”
Section: Discussioncontrasting
confidence: 99%
“…One finding in this thesis is that Actiheart recordings explained only a small fraction (6-8 %) of free-living energy expenditure above that explained by body composition variables. No comparable data exist for this age group; however, the results are in good agreement with those obtained in a study in 4-10-year-old children (85) . Explaining only an additional 6-8 % of the variation in AEE or TEE might seem low, but how much a monitor should be able to explain in order to be useful for practical application is a matter of discussion.…”
Section: Assessment Of Physical Activity and Energy Intake In Young Csupporting
confidence: 72%
“…15 A minimum duration of 6 h monitoring time per day was required to achieve proper reliability, 16 whereas the epoch of sampling was set on 15 s, where non-wear time was defined as at least 20 min of consecutive zeroes. The duration of moderate-to-vigorous physical activity (MVPA) was determined according to the cut-offs of Evenson 17 (see Konstabel et al ; 18 this issue).…”
Section: Methodsmentioning
confidence: 99%